Good time [compact disc] - Jackson, Alan, 1958-; McBride, Martina (Arista Nashville ; Distributed by Sony BMG Music Entertainment, 2008)
Jackson returns after his 2006 Gold album, Like Red on a Rose, with this 17-track effort that makes an even bigger splash in country music. Includes the great single Never Loved Before with fellow superstar Martina McBride.